Маркетингові інструменти забезпечення якості надання адміністративних послуг - Карий, О. І.; Процак, К. В.; Karyy, O.; Protsak, K. (Видавництво Львівської політехніки, 2019)
Статтю присвячено дослідженню якості надання адміністративних послуг та маркетинговим інструментам, які можуть її забезпечити. Досліджено особливості адміністративних послуг та характеристики, які відрізняють їх від інших. Розглянуто вплив інструментів маркетингу, а саме надійність, безпеку, ступінь доступності, матеріальні чинники, репутацію установи, оперативність, турботу про клієнта, ввічливість, компетентність, рівень комунікації на складові якості адміністративних послуг. Обґрунтовано критерії оцінювання якості надання адміністративних послуг. Критерії надання адміністративних послуг запропоновано поділяти на об’єктивні та суб’єктивні. Досліджено проблеми, які виникають при наданні адміністративних послуг центрами надання адміністративних послуг в Україні. Удосконалення сервісу надання адміністративних послуг передусім стосується спрощення та прозорості процедури їх надання, створення конкурентного середовища.

The article is devoted to the study of the administrative services quality and marketing tools that can provide it. Features of administrative services and characteristics which distinguish them from others are investigated. The impact of marketing tools, that is reliability, security, availability, material factors, reputation of institution, punctuality, customer care, politeness, competence, level of communication, on components of quality of administrative services are considered. In the article the criteria of evaluation concerning the work of local government (organization of the Centers of Administrative Services Provision (CNACs), provision of resource requirements (material, financial, human) for implementation of the established administrative services quality standards, etc. are considered separately. As well as the criteria relating directly to the work of the CNACs (the adequacy and reliability of information on information stands, adherence to the reception regime, the analysis of comments and suggestions, taking the necessary measures to improve the quality of services, etc.). The quality of providing administrative services depends on the technical component (imperfection of legal regulation) and the functional component, which depends directly on the process of service. The functional component is determined by such criteria as the timeliness of the provision of services, the attitude and competence of the staff, the terms of service and the condition of the premises, etc. The tools that are usually evaluated for the quality of administrative services are considered. The criteria for assessing the quality of administrative services are substantiated. It is suggested to divide the criteria for providing administrative services into objective and subjective. Problems that arise in providing administrative services by centers of administrative services in Ukraine are investigated. They were detected as a result of a survey of visitors and employees of the CNACs. It is proved that the improvement of the quality of providing administrative services mostly depends on simplicity and transparency of procedures of their provision, creation of a competitive environment.
Marketing instruments of administrative services quality assurance
Keywords: адміністративні послуги; якість послуг; маркетингові інструменти; administrative services; quality of services; marketing tools; 658.1